Determinants of serum IgG responses to periodontal bacteria in a nationally representative sample of US adults - Vlachojannis, Christian; Dye, Bruce A.; Herrera-Abreu, Miriam; Pikdöken, Levent; Lerche-Sehm, Julia; Pretzl, Bernadette; Celenti, Romanita; Papapanou, Panos N. (Journal of clinical periodontology, 2010)
To assess the distribution of elevated antibody titres to multiple periodontal bacteria, including established/putative pathogens and health-related species, by selected demographic, behavioural, and oral- and general health-related characteristics.